CO(1-0) detection of molecular gas in the massive Spiderweb Galaxy (z = 2) - Emonts, B.; Feain, I.; Röttgering, H.; Miley, G.; Seymour, Nick; Norris, R.; Carilli, C.; Villar-Martín, M.; Mao, M.; Sadler, E.; Ekers, R.; van Moorsel, G.; et al. (2013)
The high-redshift radio galaxy MRC 1138−262 (‘Spiderweb Galaxy’; z = 2.16) is one of the most massive systems in the early Universe and surrounded by a dense ‘web’ of proto-cluster galaxies. Using the Australia Telescope Compact Array, we detected CO(1–0) emission from cold molecular gas – the raw ingredient for star formation – across the Spiderweb Galaxy. We infer a molecular gas mass of MH2 = 6 × 1010 M☉ (for MH2/L′CO = 0.8). While the bulk of the molecular gas coincides with the central radio galaxy, there are indications that a substantial fraction of this gas is associated with satellite galaxies or spread across the intergalactic medium on scales of tens of kpc. In addition, we tentatively detect CO(1–0) in the star-forming proto-cluster galaxy HAE 229, 250 kpc to the West. Our observations are consistent with the fact that the Spiderweb Galaxy is building up its stellar mass through a massive burst of widespread star formation. At maximum star formation efficiency, the molecular gas will be able to sustain the current star formation rate (SFR ≈ 1400 M☉ yr−1, as traced by Seymour et al.) for about 40 Myr. This is similar to the estimated typical lifetime of a major starburst event in infrared luminous merger systems.